Trace Mineral Supplementation for the Intestinal Health of Young Monogastric Animals - Shannon, Marcia Carlson; Hill, Gretchen Myers (Frontiers in Veterinary Science, 2019)
Growth performance and feed efficiency are essential parameters when evaluating profitability of livestock. However, animal performance does not always reflect optimal gut health. Decades of research has supported the theory that improved animal performance such as average daily gain and feed efficiency can be impacted by intestinal health or the ability of the intestinal mucosa to absorb nutrients, but dysfunction may be found when the animal is stressed. Most of the early research focused on enteric infections causing diarrhea and nutritional alternatives to antibiotics which has led to findings related to pharmacological supplementation of trace minerals above the nutrient requirements for non-ruminants. While pharmacological concentrations of copper (Cu) have been shown to enhance growth, the mechanism in the gut is elusive. High concentrations of zinc (Zn) fed to newly weaned nursery pigs reduced the incidence of diarrhea from the proliferation of enterotoxigenic Escherichia coli (E. coli) and Clostridium. There are numerous publications where pharmacological supplementation of Zn as zinc oxide (ZnO) were fed to newly weaned pigs. Pharmacological Zn has been reported to shape the intestinal microflora as well as the diversity of the microflora during the first 2 weeks post-weaning. Both Fe deficiency and fortification impact bacterial growth in the intestine. Therefore, this paper will focus on the role of trace minerals that potentially impact optimal gut health of young monogastric animals.